Oviposition dynamics of Aedes aegypti in Central Argentina. Issue 1 (7th October 2021) - Sánchez‐Díaz, E.; Gleiser, R. M.; Lopez, L. R.; Guzman, C.; Contigiani, M. S.; Spinsanti, L.; Gardenal, C. N.; Gorla, D. E.
Abstract: Aedes (Stegomyia) aegypti (L.) (Diptera: Culicidae) is the vector of multiple arboviruses. To evaluate the association between environmental factors and the oviposition activity of Ae. aegypti in Argentina, data on the presence and abundance of eggs were collected using ovitraps, between September of 2018 and May of 2019, in the cities of Villa María, Río Cuarto and Salsipuedes (Córdoba province, Argentina). We analysed the relationships between oviposition and five environmental factors: Temperature, precipitation, vegetation cover, human population density and distance to sites with a potential high density of larval habitats, like cemeteries and trash dumps. Environmental factors' data were collected using satellite image products. The oviposition activity was randomly distributed in three cities. Using generalized linear mixed models, we show that the house where each ovitrap was placed was a source of variability in oviposition, suggesting the relevance of microsite factors and the importance of domestic control actions. Ae. aegypti oviposition was positively correlated with night‐time temperature of the previous 3 weeks, and in a context‐dependent manner, it was positively correlated with human population density, vegetation cover and precipitation. The consistency and magnitude of these relationships varied between cities, indicating that oviposition is related to a complex system of environmental variables. Abstract : Data on Aedes aegypti (L.) oviposition indicate that the reproductive activity of this dengue vector was randomly distributed in the three cities surveyed in Córdoba province (Argentina). The house where each ovitrap was placed was a source of variability in oviposition, suggesting the relevance of microsite factors and the importance of domestic control actions. A. aegypti oviposition was positively correlated with night‐time temperature, human population density, vegetation cover and precipitation. The consistency and magnitude of these relationships varied between cities.